PENINGKATAN KEMAMPUAN BERCERITA MELALUI MENGGAMBAR BEBAS PADA ANAK KELOMPOK B TK LKIA II PONTIANAK - Isti Punamasari; Aloysius Mering; Usman Radiana (Universitas Tanjungpura, 2020)
AbstractThis study aims to improve the ability to tell storiesthrough free drawing in group B TK LKIA II Pontianak. The research method used is descriptive. The research approach uses a qualitative appoarch and the form of this research is action research assisted by the class teachers as collaborator. The subjects of the study were children of group B (5-6 years) totaling 16 people consisting of 3 women dan 13 men. Data collection techniques used in this study were observastion and documentation, while data collection tool was an observation sheets and documentation. This research was conducted in two cycles with assessment criteria, namely to tell pictures that were made and express words clearly. The abilty to tell pictures made in the first cycles was 12,5%, then increased in the second cycle to 81,25% and the ability to express word clearly in the first cycle by 25%, then increased in the second cycle to 87,5%. Based on the study an increase in the ability to tell stories through free drawing in group B TK LKIA II Pontianak. So the implication is that the teacher can apply free drawing activities to improve chilldren’s storytelling abilities. Keywords:Storytelling Ability, Free Drawing, Children Aged 5-6 Years